Respostas
respondido por:
1
Fórmula =========> An = A¹ + (n - 1) . r
-45 = 17 + ( 32 - 1) . r
-45 - 17 = 31r
-62 = 31r
r = -62/31 = -2
Espero ter ajudado!
-45 = 17 + ( 32 - 1) . r
-45 - 17 = 31r
-62 = 31r
r = -62/31 = -2
Espero ter ajudado!
respondido por:
0
Olá, boa noite ☺
Resolução:
An = a1 +(n-1).r.
Substituindo valores...
-45 = 17 + (32-1).r.
-45 = 17 + 31r.
31r=-17 -45.
31r=-62
r=-62/31
r = -2 --> Resposta
Bons estudos :)
Resolução:
An = a1 +(n-1).r.
Substituindo valores...
-45 = 17 + (32-1).r.
-45 = 17 + 31r.
31r=-17 -45.
31r=-62
r=-62/31
r = -2 --> Resposta
Bons estudos :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás